Lived experiences and coping responses toward mandatory quarantine among Malaysian healthcare workers during COVID-19 pandemic : a qualitative analysis - Chew, Keng Sheng; Nuraini Ibrahim,; Nur Afiqah Mohd Fazillah,; Dharshinni Subramaniam,; Asher Vikki Sibey,; Farrah Nabilah Silaiman,; Ivy Melissa Woa,; Nurul Azimah Rukyno, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper describes the lived experiences and coping responses towards mandatory quarantine among Malaysian healthcare workers who were exposed to the risk of COVID-19 infection during the first phase of movement control order. To capture the rich and thick description of these experiences, interpretative phenomenological approach using in-depth interview was employed. Due to the cordon sanitaire imposed, all interviews were conducted online either through a video conferencing application or through an online survey platform. A total of 11 participants responded. The interview contents were transcribed and iteratively coded by the authors independently. Four broad themes emerged. First, most participants accepted well on the need for mandatory quarantine. They understood the importance of quarantine in containing and breaking the chain of infection. Second, the most distressful moment was the waiting period for the result of their first nasopharygeal swab. Third, boredom was a major triggering factor resulting in the germination and rumination of negative thoughts. Fourth, although conspicuously absent in published literature from Western countries, religious faith appeared to be one of the most important coping mechanisms for our Muslim and Christian participants. To combat boredom and to refrain from dwelling on negative thoughts, they devoted their time to prayers and reading religious scriptures.